E-040 Analysis of the SPAN-100 Index as a Predictor of Clinical Outcome in the Post-Marketing North American SOLITAIRE Stent-Retriever Acute Stroke Registry. (26th July 2014) - Castonguay, A; Zaidat, O; Novakovic, R; Gupta, R; Sun, C; Martin, C; Holloway, W; Mueller-Kronast, N; English, J; Linfante, I; Dabus, G; Malisch, T; et al.
Abstract : Background: In light of the negative results of three randomised trials for endovascular acute ischemic stroke therapy, proper patient selection has become a critical area of focus for endovascular therapy. The Stroke Prognostication using Age and NIH Stroke Scale (SPAN) index, a score that combines age and NIHSS, demonstrated that SPAN-100 positive patients did not benefit from IV-tPA. Here, we sought to evaluate the predictive value of SPAN index in a real-life cohort of patients undergoing endovascular therapy. Method: Using data from the investigator-initiated, multicenter North American Solitaire Stent-Retriever Acute Stroke (NASA) Registry, the SPAN index was calculated for each patient (age plus NIHSS). A cohort of SPAN-100 positive (SPAN ≥ 100) patients was identified and compared to SPAN-100 negative (SPAN <100) patients. Successful recanalization was defined as Thrombolysis in Myocardial Infarction (TIMI) ≥2. Good clinical outcome was defined as a 90-day mRS ≤ 2. Results: Of 354 patients in the NASA Registry, 308 had available baseline NIHSS scores and 90-day mRS scores. 68/354 (22.1%) patients were SPAN-100 positive. Mean age of patients that were SPAN-100 positive was 83.9 ± 5.6 years vs. 62.8 ± 13.3 years in the SPAN-100 negative cohort (p = < 0.0001). No difference was seen in the rate of successful reperfusion (TIMI ≥ 2) among the groups (p = 0.9). Only 26.5% (18/68) of patients in the SPAN-100 positive cohort had a 90-day mRS ≤ 2 vs. 47.1% (113/240) of those SPAN-100 negative (p = 0.002). Mortality was 50.0% (34/68) and 24.6% (59/240) in SPAN-100 positive and SPAN-100 negative, respectively. In a multivariate analysis, SPAN-100 positive was shown as an independent predictor of clinical outcome, with 2.5 times greater likelihood of worse outcome versus those with SPAN-100 negative (OR 2.5; 95% CI 1.3–5.1; p = 0.006). Conclusion: Analysis of the NASA Registry demonstrated that SPAN-100 positive is significantly associated with worse clinical outcome and higher mortality rate at 90 days compared to SPAN-100 negative patients. SPAN-100 was shown as an independent predictor of clinical outcome and may be useful tool in the selection of patients for endovascular therapy. Disclosures: A. Castonguay: None. O. Zaidat: 1; C; Stryker Neurovascular, Covidien Neurovascular. 2; C; Covidien Neurovascular. R. Novakovic: None. R. Gupta: None. C. Sun: None. C. Martin: None. W. Holloway: None. N. Mueller-Kronast: None. J. English: None. I. Linfante: None. G. Dabus: None. T. Malisch: None. F. Marden: None. H. Bozorgchami: None. A. Xavier: None. A. Rai: None. M. Froehler: None. A. Badruddin: None. T. Nguyen: None. M. Taqi: None. M. Abraham: None. V. Janardhan: None. H. Shaltoni: None. A. Yoo: None. A. Abou-Chebl: None.